Relationship between parenting style and physical activity participation among adolescents - Mohamed, Ani Mazlina Dewi; Missnan, Nurul Atikah; Norjali Wazir, Mohd Rozilee Wazir (Atlantis Press, 2019)
Parents play an important role in the development of healthy lifestyle behaviors in their children. Therefore, this study was conducted to determine the relationship between parenting style and physical activity participation. A random 100 student’s aged range from 13 to 17 years old were selected as respondents of this study. The Physical Activity Questionnaire for Adolescences (PAQ-A) was used as the instrument to measure respondent's general level of physical activity meanwhile the Parenting Style Questionnaire (PSQ) was used to assessed respondent's perceived parenting style of their parents. The results showed that majority of adolescent were involved in moderate level of physical activity and only 29% reported to be very active during physical education class and 40% claimed that they did not active after school hour. Data analysis also showed that 60% of the respondents perceived the parents are using authoritative style, authoritarian style (31%) and permissive style (9%). Finally, the statistical analysis showed that there is a significant relationship between parenting style and physical activity participation thus conclude parenting styles play as a role in the promotion and involvement of physical activity among adolescents.